Organelle Isolation for Proteomics: Mitochondria from Peripheral Blood Mononuclear Cells - Pooreydy, Bahram; Jafari, Mohieddin; Tajik, Faezeh; Karimi, Mehrdad; Rezaei-Tavirani, Mostafa; Ghassempour, Alireza; Rezadoost, Hassan; Khodabandeh, Mahvash (Archives of Advances in Biosciences, 2013)
Mitochondria play key roles in many cell functions including energy production, fatty acid metabolism, pyrimidine biosynthesis, calcium homeostasis, and aging. They also regulate crucial signaling cascades such as apoptosis and oxidative stress. The proteome is often used to investigate the functional correlations on protein levels. Based upon the human, genome there is estimated 2000 to 2500 associated mitochondrial proteins, however, just over 600-800 have been identified at the protein level. For this reason, mitochondria contain a great number of proteins that have yet to be identified and characterized. The identification of these proteins can help in discovery of biological process. This protocol focuses on step-by-step procedure of mitochondrial proteome extraction from peripheral blood mononuclear cell (PBMC) mitochondria. The isolation and preparation procedures described here require 6 hours approximately.